TODUŢĂ’S “ANTIQUES” - Ecaterina BANCIU (Studia Universitatis Babeş-Bolyai. Musica)
Delightful musical pages, the Concerto no. 3 for string orchestra “in stile antico”, Old engravings for string orchestra and the Sinfonietta “in antico stile” by Sigismund Toduţă are among the “classical” works due to the ingenuity of the modal, poly-metric themes, with a local, jovial or elegy-like air, imprinted on the most elaborate patterns of variational forms, imitative polyphonic or with refrain and rendered by extremely refined orchestration. The purpose of the present paper was to reveal the relation between these works and the universality of their language.